Primary Cutaneous Anaplastic Large Cell Lymphoma Arising in a Patient with Rhupus Syndrome and Sjogren’s Syndrome - Gao Z; Xu Q; Chen X; Mao D; Zhang J; Jin J (Dove Medical Press, 2022)
Zirui Gao, Qianxi Xu, Xue Chen, Dandan Mao, Jianzhong Zhang, Jiang Jin Department of Dermatology, Peking University People's Hospital, Beijing, People's Republic of ChinaCorrespondence: Jiang Jin, Department of Dermatology, Peking University People's Hospital, No. 11 Xizhimen South Street, Xicheng District, Beijing, 100044, People's Republic of China, Email PUPH_JiangJin@163.comAbstract: Rhupus syndrome, as an overlap syndrome of rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), is relatively rare because of their substantially different immunopathological mechanisms. Herein, we report the first case of primary cutaneous anaplastic large cell lymphoma (PC-ALCL) in a patient with rhupus syndrome and Sjogren's syndrome and review the relevant literature. A 52-year-old Chinese woman with a history of rhupus syndrome and Sjogren's syndrome was treated with methotrexate, who developed gradually increasing nodules on the waist. Histopathological studies showed that the dermis and subcutaneous tissue were infiltrated with medium-to-large, atypical lymphocytes with the oval nucleus. The tumor cells showed CD3-, CD4-, CD8-, CD30+, LCA+, and EBV-encoded RNA (EBER) in situ hybridization (ISH) was positive. Therefore, the patient was diagnosed with PC-ALCL. Both immune disorders and EBV infection may be related to the onset of PL-ALCL, and further studies are needed to clarify the pathogenesis.Keywords: lymphoproliferative disease, rheumatoid arthritis, systemic lupus erythematosus, Sjogren's syndrome, methotrexate